1998
DOI: 10.1212/wnl.51.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of valproate and phenobarbital treatment after status epilepticus in rats

Abstract: The long-term consequences of AED treatment during development are related to the drug used. VPA treatment after KA-induced status epilepticus prevents many of the neurologic sequelae typically seen after KA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 23 publications
6
57
1
1
Order By: Relevance
“…This disease-modifying effect of phenobarbital was unexpected, because prolonged administration of phenobarbital in juvenile rats did not alter the development of SRS in the kainate model of TLE ( Bolanos et al, 1998). However, in the present study, treatment with phenobarbital was started 90 min after onset of SE, whereas Bolanos et al (1998) started treatment with phenobarbital 24 h after onset of SE, so that the therapeutic window of opportunity may have been missed. Thus, one novel and important finding of the present study is that prophylactic treatment with phenobarbital after a brain insult such as SE modifies the development of epilepsy.…”
Section: Discussionmentioning
confidence: 56%
“…This disease-modifying effect of phenobarbital was unexpected, because prolonged administration of phenobarbital in juvenile rats did not alter the development of SRS in the kainate model of TLE ( Bolanos et al, 1998). However, in the present study, treatment with phenobarbital was started 90 min after onset of SE, whereas Bolanos et al (1998) started treatment with phenobarbital 24 h after onset of SE, so that the therapeutic window of opportunity may have been missed. Thus, one novel and important finding of the present study is that prophylactic treatment with phenobarbital after a brain insult such as SE modifies the development of epilepsy.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, it has been reported previously that patients with TLE display deficits in recognition memory (for review, see Elger et al, 2004). In addition, a previous study showed the prevention of cognitive impairment after KAinduced seizures by VPA treatment using the Morris water maze (Bolanos et al, 1998). Therefore, the inhibition of aberrant seizure-induced neurogenesis and the morphological normalization of neurons that were generated in response to SE by VPA treatment might at least partially explain the observed protection from seizure-associated cognitive impairment.…”
Section: Discussionmentioning
confidence: 86%
“…The present study with LEV shows that interesting results can be obtained by drug testing in epileptic rats, which are much closer to data from clinical evaluation of this drug in patients with epilepsy than are data from short-term drug testing in traditional seizure models, in which only elicited seizures are examined. In addition to using models with spontaneous recurrent seizures, such as the pilocarpine or kainate models, for evaluation of AED effects during prolonged treatment, these models also can be used to evaluate antiepileptogenic drug effects by starting treatment shortly after the SE (34,35). Automated seizurerecording systems, including EEG monitoring via telemetric devices, will certainly make long-term studies in such models less labor dependent and increase the use of epileptic animals for evaluation of anticonvulsant and antiepileptogenic drug effects.…”
Section: Discussionmentioning
confidence: 99%